The Impact of Associating Images with Text on Child Education during the Primary School Stage - Al-Ramahi, Asst. Lecturer Noor Ali Mohammed Al-Ramahi (Sulaimani Journal for Humanities, 2026)
Education at the primary stage is the fundamental cornerstone in shaping human behavior. Therefore, it must be given due attention and should not be neglected or treated as secondary to academic learning. This necessity led us to search for the most effective method to guide and modify children's behavior, especially when they are subjected to psychological pressures from family and society. The image is a communicative tool that should not be underestimated compared to other means of communication. It is, in fact, the first spiritual communicative medium between the child and the surrounding external world during early childhood—based on what the child sees even before understanding it. Over time, visual images become associated with the behaviors of those around them—such as joy, sadness, contentment, acceptance, anger, and other emotional responses—which the brain interprets through both the right and left hemispheres.
Keywords: Text; Image; Communication Tools; Association; Education